2018
DOI: 10.1523/jneurosci.3350-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor 4 (ATF4) Regulates Neuronal Activity by Controlling GABABR Trafficking

Abstract: Activating Transcription Factor 4 (ATF4) has been postulated as a key regulator of learning and memory. We previously reported that specific hippocampal ATF4 downregulation causes deficits in synaptic plasticity and memory and reduction of glutamatergic functionality. Here we extend our studies to address ATF4's role in neuronal excitability. We find that long-term ATF4 knockdown in cultured rat hippocampal neurons significantly increases the frequency of spontaneous action potentials. This effect is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…In addition, signals mediating the activated PKC-δ neurons to the SNS, remain unclear in light of our study's results. Our results showed that deletion of GCN2 in the amygdala stimulated the activity of PKC-δ neurons, which might be mediated by increasing ATF4 expression which induces neuronal firing, as previously shown 50,51 . PKC-δ neurons are a class of GABAergic neurons, and activation of PKC-δ neurons increases GABA release thus inhibiting feeding 21 .…”
Section: Discussionsupporting
confidence: 84%
“…In addition, signals mediating the activated PKC-δ neurons to the SNS, remain unclear in light of our study's results. Our results showed that deletion of GCN2 in the amygdala stimulated the activity of PKC-δ neurons, which might be mediated by increasing ATF4 expression which induces neuronal firing, as previously shown 50,51 . PKC-δ neurons are a class of GABAergic neurons, and activation of PKC-δ neurons increases GABA release thus inhibiting feeding 21 .…”
Section: Discussionsupporting
confidence: 84%
“…Studies have shown that ATF4 directly interacts with GABA B receptors in the soma and at the dendritic membrane surface of both cultured hippocampal neurons and retinal amacrine cells [41][42][43] . Research has also shown that knocking down ATF4 significantly decreases the membrane expression of GABA B receptors but does not change the total abundance of GABA B receptors in hippocampal neurons, indicating that ATF4 regulates GABA B receptor trafficking 44 . Therefore, despite being a transcription factor, ATF4 may also be involved in nontranscriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the interaction between fibulin-2 and the Sushi domains may also interfere with the receptor trafficking and regulate GABAB inhibition as demonstrated for ATF4, another interactor ( Corona et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%